Transport Systems: Safety Modeling, Visions and Strategies - Goniewicz, Krzysztof; Czerski, Robert; Kustra, Marek (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint includes papers describing the synthesis of current theory and practice of planning, design, operation, and safety of modern transport, with special focus on future visions and strategies of transport sustainability, which will be of interest to scientists dealing with transport problems and generally involved in traffic engineering as well as design, traffic networks, and maintenance engineers.